Cultural and linguocognitive representations of the concepts of the happiness and the heart in English and Uzbek: a comparative study of Judith Mcnaught’s literary discourse - Usmonova, Zarina Habibovna; Abduraxmonova, Dilorom O‘tkir qizi; Shuhratov, Shuhratbek Shoxmat o‘g‘li (The Lingua Spectrum, 2026)
This article examines the cultural and linguocognitive representation of the concepts of happiness and heart in English and Uzbek through a comparative analysis of literary discourse, focusing on selected works by Judith McNaught. The study is based on cognitive linguistics and cultural linguistics, especially Conceptual Metaphor Theory developed by George Lakoff and Mark Johnson. Its main aim is to explore how emotional concepts are structured, conceptualized, and expressed in different cultural contexts. Using qualitative methods such as semantic, conceptual, and contextual analysis, the research investigates lexical units, metaphorical expressions, and phraseological constructions related to happiness and heart in English literary texts and their Uzbek equivalents. The findings reveal that both languages share universal cognitive patterns, such as linking happiness with warmth and emotional fullness, while differing in cultural interpretations and symbolic meanings. The study contributes to cross-cultural semantics, translation studies, intercultural communication, and language teaching.